Impact on Workers’ Health While Extracting the Fibre of Castor Stalks – A Case Study - Lakshmi, V.Vijaya; Deepika , J. (European Journal of Applied Sciences, 2021)
Fibre is extracted from various natural sources i.e. both plant and animal. However lot of research is being done in identifying new plant materials to extract fibre in order to manufacture organic fabric for environment sustainability. So far various plant sources have been identified for fibre extraction from either of the parts like stem, leaves and seeds of sisal, cotton, coir, bamboo, weeds etc. In this context, Clothing and textiles department of Professor Jayashankar Telangana state agricultural university has extracted fiber from castor stalks for fabric making. Fiber was extracted manually which was a laborious process. Hence the present study has made an attempt in understanding the drudgery experienced by workers in extracting the fibre and measures to reduce their occupational health hazards. Case study approach was adapted to understand the procedure followed in fibre extraction, musculoskeletal discomforts faced by the workers and muscle fatigue analysis. Cuts and scratches on hands and legs occurred when stalks were collected, breathlessness, chest tightness, vomiting sensation, headache and coughing were experienced during the soaking of stalks due to strong smell, task was found to be at very high risk in different body parts. Hence, fibre extraction task was not at all acceptable and there is a need to change the working procedure and improve the posture to improve their health status.